Biotechnological innovations in chemical synthesis. - Balken, J. A. M. van (Biotechnology by Open Learning (Series), 1997)
A self-study textbook for technicians seeking further education, graduates extending their knowledge base, experienced workers facing changes in jobs, managers unfamiliar with the new technology, and people returning after a career break. Explores some ways biotechnology can provide new routes for producing traditional organic chemical products and enable new products to replace those with environmental or other drawbacks. The aspects discussed include a biocatalyst in organic synthesis, the efficiency of growth and product formation, the production and diversification of antibiotics, and the industrial production of amino acids by fermentation and chemo-enzymatic methods.